Cindrella - Kelly; Miles (Essex Miles Kelly, 2015)
The Brothers Grimm Cinderella and other stories is a beautifully illustrated storybook for children aged 5+. Containing four famous favourites by master storytellers the Brothers Grimm, young readers will discover a world of imagination and adventure within. This book has a stunning sparkly cover, making it an ideal gift for fairy tale fans. Stories included: Cinderella, The Spirit in the Bottle, the Glass Coffin, The Magic Porridge Pot.